P-277 Palliative care volunteers in europe: qualitative analysis of volunteer activities and experiences. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Scott, Ros; Goossensen, Anne; Payne, Sheila; Pelttari, Mag Leena
Abstract : Background: Volunteers are an essential and integral part of hospice and palliative care (HPC) in many countries. It is often others, rather than volunteers, who report their activities and experiences. Led by the European Association for Palliative Care (EAPC) Task Force in Volunteering, this project aimed to give volunteers a voice and to invite their personal stories of involvement in HPC in their own words. Aims: The aims were to understand: the experiences of volunteers in HPC; why they work in HPC; what volunteering in this field means to them. Method: Task Force members in seven countries were asked to invite five volunteers to write about their volunteering activities and experiences in their own language. Two prompt questions were given to volunteers: 'What do you do as a volunteer?' and 'What does it mean to you?' Stories were translated into English and a qualitative framework used for analysis. Results: In total, 37 stories of 400–500 words were received from eight countries. Almost all (n=34) volunteers offered practical, emotional, social and spiritual support to adult patients and families. 32 were involved in diverse adult HPC settings including patients' homes, hospices, hospitals and care homes and two in community children's palliative care All found significant meaning in HPC volunteering, described as an important part of their life and values Volunteers described the privilege of being with people at end of life and how much they learn from encounters with death and dying. Others highlighted the challenges of HPC volunteering and how their lives are enhanced by their experience. Conclusion: The narratives gave an insight into the personal stories of volunteers in different countries and highlighted many similarities in shared experiences and values. Understanding these perspectives can help HPC organisations to improve how volunteers skills may best be utilised and supported.